Personality assessment in orthopaedic residency programs: A cross-sectional survey study. Issue 2 (March 2020) - Salazar, Dane; McGregor, Patrick Cole; Varsanik, Mary Alyssa; Perry, Michael; Schiff, Adam
Abstract : Background: The use of personality-based assessments has become common practice across industries outside of medicine. Although widely used in the corporate arena, the use of personality testing in medicine is comparatively unexplored. The objective of this study was to investigate the prevalence of personality assessment tools used by orthopaedic residency programs. Methods: Survey invitations were sent to 154 orthopaedic residency program directors from around the United States. The survey queried the use of personality assessment tools in each residency program. Participants also were asked their sentiments regarding the potential utility of personality assessment in their respective programs. Results: Of the 47 respondents, 42 program directors indicated they do not use any personality assessment in their residency program. Of the five directors answering in the affirmative, three use personality assessment to identify potential problems, two use it for mentorship selection and for investigational purposes. One director uses personality assessment in the evaluation of residency applicants. No program directors use the information to select clinical service teams. A majority indicated they are at least somewhat familiar with the Myers-Briggs personality inventory. Conclusions: Personality assessment is not a widely used tool in orthopaedic residency programs, with nearly 90% of program directors indicating they do not use it in their programs. However, nearly 70% of respondents indicated there is some utility for the use of personality testing in their residency. Future studies will be needed to further elucidate the barriers to wider spread utilization of personality assessment. Level of Evidence: Level IV.